The effect of size reduction and different oil ratio on microemulsion of trigonella foenum-graceum and phyllanthus embilica oils and their antioxidant properties - Mohd Yazid, Muhammad Saiful Asri; Mansur, Sity Aishah (2024)
This study aims to develop a hair tonic using micro-sized fenugreek and amla seed oils to treat premature greying of hair (PGH). The prevalence of this problem in young people is concerning, and existing solutions like hair dye have limitations. Fenugreek and amla seed oils possess antioxidant and hair-beneficial properties, and size reduction for both oils can enhance their effects. Ultrasonication will be used to create micro-sized oils, then tested for physicochemical properties, antioxidant activities, and the storage stability. Young people are increasingly facing hair issues like premature greying, yet current solutions like expensive transplants and potentially harmful dyes leave them wanting a much cheaper and safer solution. Existing haircare products often contain concerning ingredients, and even PGH treatments like dyes may have negative effects. The aim to use ultrasonication method, a technique used in drug formulations, is to create stable combined fenugreek and amla seed oils micro-emulsions for hair products, potentially providing a safer and more effective solution for hair problems like PGH. The method of the research is to use ultrasonication technique to reduce the particles size of the oil emulsion into smaller size ranging into the micro-sized region (0.7 to 700 micrometers), and to determine the particle size, Zeta Potential Analyzer (ZetaSizer) is used. From the result obtained, the second formulation for 1:1 ratio of fenugreek to amla seed oils which has higher water content, has the most significant size reduction of 88.93%. In conclusion, ultrasonication method does promises the size reduction for oil emulsions, and the result could be enhanced by adding centrifuge, and sieving method to further purify the oil emulsion creating a smaller particle size